Six Minutes of Physical Activity Improves Mood in Older Adults: A Pilot Study. Issue 1 (January 2021) - Boolani, Ali; Sur, Shantanu; Yang, Da; Avolio, Abby; Goodwin, Aurora; Mondal, Sumona; Fulk, George; Towler, Christopher; Lee Smith, Matthew
Abstract : Background and Purpose: The purposes of this study were to examine (1) differences in mood and motivation among older adults after the completion of 6 minutes of self-paced walking (6MW) and (2) the relationship between pace and magnitude of mood change. Methods: Eleven participants completed 3 days of testing where energy, fatigue, tension, depression, confusion, mental and physical energy, and motivation to perform mental tasks were measured before and after the 6MW. A repeated-measures analysis of variance was used to examine changes in mood and motivation, and a bivariate Pearson correlation was used to determine relationships between pace and magnitude of changes in mood. Results: Faster pace was associated with significant improvements ( P < .05) in fatigue, energy, tension, confusion, total mood disturbance, state mental fatigue, and state physical energy. A significant relationship was noted between pace and changes in energy, fatigue, state mental and physical energy, and fatigue in the expected direction. Discussion: Results indicate that mood is influenced by pace of the activity. Findings suggest that even 6 minutes of physical activity can improve moods, which may impact how physical therapists approach prescribing exercise to older adults. Abstract : Supplemental Digital Content is Available in the Text.